Northwest Africa 4797; a strongly shocked ultramafic poikilitic shergottite related to compositionally intermediate Martian meteorites - Walton, Erin L.; Irving, A. J.; Bunch, T. E.; Herd, Christopher D. K. (My University, 2012)
Northwest Africa (NWA) 4797 is an ultramafic Martian meteorite composed of olivine (40.3 vol%), pigeonite (22.2%), augite (11.9%), plagioclase (9.1%), vesicles (1.6%), and a shock vein (10.3%). Minor phases include chromite (3.4%), merrillite (0.8%), and magmatic inclusions (0.4%). Olivine and pyroxene compositions range from Fo (sub 66-72) ,En (sub 58-74) Fs (sub 19-28) Wo (sub 6-15) , and En (sub 46-60) Fs (sub 14-22) Wo (sub 34-40) , respectively. The rock is texturally similar to "lherzolitic" shergottites. The oxygen fugacity was QFM-2.9 near the liquidus, increasing to QFM-1.7 as crystallization proceeded. Shock effects in olivine and pyroxene include strong mosaicism, grain boundary melting, local recrystallization, and pervasive fracturing. Shock heating has completely melted and vesiculated igneous plagioclase, which upon cooling has quench-crystallized plagioclase microlites in glass. A mm-size shock melt vein transects the rock, containing phosphoran olivine (Fo (sub 69-79) ), pyroxene (En (sub 44-51) Fs (sub 14-18) Wo (sub 30-42) ), and chromite in a groundmass of alkali-rich glass containing iron sulfide spheres. Trace element analysis reveals that (1) REE in plagioclase and the shock melt vein mimics the whole rock pattern; and (2) the reconstructed NWA 4797 whole rock is slightly enriched in LREE relative to other intermediate ultramafic shergottites, attributable to local mobilization of melt by shock. The shock melt vein represents bulk melting of NWA 4797 injected during pressure release. Calculated oxygen fugacity for NWA 4797 indicates that oxygen fugacity is decoupled from incompatible element concentrations. This is attributed to subsolidus re-equilibration. We propose an alternative nomenclature for "lherzolitic" shergottites that removes genetic connotations. NWA 4797 is classified as an ultramafic poikilitic shergottite with intermediate trace element characteristics.
Keywords: achondrites; chain silicates; crystallization; electron probe data